Financing the embedded value of life insurance portfolios - Luise Hölscher; Perham Harding; Gernot M. Becker (HfB - Business School of Finance & Management, 2005)
In May 2004 the CFO Forum harmonized the various efforts of reporting the embedded valueof life insurance companies by issuing the European Embedded Value (EEV) Principles.In this working paper a methodology is proposed to derive a maximum lending amountfrom EEV figures without much additional data requirements from the originating insurer. The approach chosen is similar to that of other financing areas, e.g. real estate finance, where first a prudent best estimate valuation is done and later risk deductions are performed in the form of applying loan to value ratios, e.g. 60-80 % of the prudent amount. Here, this prudent value is called bankable embedded value and the loan to value analysis presented leads to the maximum lending amount. The deductions proposed to arrive at a maximum lending amount are based on parameter adjustments and risk allowances for unexpected risks. There is an analogy with insurers for determining their own capital needs. The methodology proposed is based on the stress test approach which increasingly gains popularity with insurance supervisors in Europe.
urn:nbn:de:101:1-20080825154
Keywords: G22; M41; 330; European embedded value; embedded value; life insurance policies; maximum lending amount; required capital; risk analysis; risk discount rate; value reporting and analysis; value sensitivity analysis